Management Innovation in Building Independence Educational Institutions - Mubarok, Ramdanil (Jurnal El-Hamra : Kependidikan dan Kemasyarakatan, 2024)
This research examines building educational independence through management innovation. The aim is to analyze the concept of management innovation, management innovation in building the independence of educational institutions, as well as problems in building the independence of educational institutions. The method applied in this research is the library research method. The research results are: The concept of management innovation often emphasizes the importance of innovation as the key to improving organizational performance and maintaining competitiveness in a dynamic environment. Meanwhile, building the independence of educational institutions can be done by: developing vision, mission, and strategy; efficient resource management; developing leadership and managerial skills; using technology to improve performance; and developing strategic partnerships. The problems are: limited financial resources, dependence on government funds or donors, limited access to technology and infrastructure, lack of managerial skills among staff and leaders of educational institutions, changes in government policy, and lack of community support. It is hoped that this research will provide valuable insight for education policy makers, teaching staff, and other stakeholders in their efforts to strengthen the educational institution system and prepare educational institutions that are strong and competitive. Keywords: Innovation, Management, Independence, Educational institutions Penelitian ini mengkaji tentang membangun kemandirian pendidikan melalui inovasi manajemen. Tujuannya adalah untuk menganalisis konsep inovasi manajemen, inovasi manajemen dalam membangun kemandirian lembaga pendidikan, serta problem dalam membangun kemandirian lembaga pendidikan. Metode yang diaplikasikan dalam penelitian ini adalah metode penelitian kepustakaan. Hasil penelitian yaitu: Konsep inovasi manajemen sering kali menekankan pentingnya inovasi sebagai kunci untuk meningkatkan kinerja organisasi dan mempertahankan daya saing di lingkungan yang dinamis. Sementara dalam membangun kemandirian lembaga pendidikan dapat dilakukan dengan: pengembangan visi, misi, dan strategi, pengelolaan sumber daya yang efisien, pengembangan kepemimpinan dan keterampilan manajerial, penggunaan teknologi untuk peningkatan kinerja, penggunaan teknologi untuk peningkatan kinerja, dan pengembangan kemitraan strategis. Adapun problemnya adalah: keterbatasan sumber daya finansial, ketergantungan pada dana pemerintah atau donatur, keterbatasan akses terhadap teknologi dan infrastruktur, kurangnya keterampilan manajerial di antara staf dan pimpinan lembaga pendidikan, perubahan kebijakan pemerintah, dan kurangnya dukungan masyarakat. Harapannya, penelitian ini akan memberikan wawasan yang berharga bagi para pengambil kebijakan pendidikan, tenaga pendidik, dan stakeholder lainnya dalam upaya mereka untuk memperkuat sistem lembaga pendidikan dan mempersiapkan lembaga pendidikan yang tangguh dan berdaya saing. Kata kunci: Inovasi, Manajemen, Kemandirian, Lembaga Pendidikan